High-Speed Reduction of Triarylpyrylium Salts Using Zn(BH4)2/SiO2 as an Efficient and Regiospecific Reducing Reagent - Arash Mouradzadegun; Ali Reza Kiasat; Somayeh Elahi (Journal of Chemistry)
The regiospecific reduction of some triarylpyrylium salts in the presence of modified hydride donors was investigated. Among these reagents, Zn(BH4)2/SiO2 performed the best results. The major advantages of this reagent are the cheapness, availability, simplicity in operation, very short reaction time and much improved regioselectivity in comparison with the other reducing reagents.